Providing care to refugees through mainstream general practice in the southern health region of New Zealand: a qualitative study of primary healthcare professionals’ perspectives - Tim Stokes; Lauralie Richard; Chrystal Jaye; Georgia Richardson (BMJ Open)
Objective To explore the perspectives of primary healthcare (PHC) professionals providing care to refugees through mainstream general practice.Design Qualitative exploratory design with semistructured interviews subjected to inductive thematic analysis.Setting and participants Nine general practices enrolled in the Dunedin Refugee Resettlement Programme, in New Zealand (NZ)’s southern health region. Participants included nine general practitioners and six practice nurses.Results Three analytical constructs were identified: relational engagement with refugees, refugee healthcare delivery and providers’ professional role shaped by complexity. Building meaningful relational connections involved acknowledging refugees’ journeys by getting to know them as people. This was instrumental for the development of an empathetic understanding of the complex human trajectories that characterise refugees’ journeys to NZ. Participants encountered challenges in providing care to refugees with respect to time-limited consultations, variable use of interpreter services, fragmentation of care between agencies and need for improved health infrastructure to ensure a fluid interface between PHC, secondary care and community support services. The current business model of NZ general practice was perceived to interfere with value-driven care and discouraged tailoring of care to specific patient groups, raising concerns about the ‘fit’ of mainstream general practice to address the complex healthcare needs of refugees. Meeting the needs of refugees across the social determinants of health involved a lot of ‘behind the scenes work’ particularly in the absence of shared information systems and the lack of well-established referral pathways to connect refugees to services beyond the health sector. This led to providers feeling overwhelmed and uncertain about their ability to provide appropriate care to refugees.Conclusions This study provides rich context-specific findings that enhance PHC responsiveness to the needs of refugees in NZ.